Intraductal Papilloma: Atypical Presentation - P. Ramaswamy; Tanya Khaitan; A. Anuradha; B. Praveen Kumar; S. Sudhakar (Hindawi Limited, 2013)
Ductal papillomas have unique papillary features arising from the salivary gland duct system. They comprise three rare benign adenomas, namely, inverted ductal papilloma, sialadenoma papilliferum, and intraductal papilloma. Intraductal papilloma is an extremely rare benign salivary gland tumor that occurs most commonly in the minor salivary glands. Here, we are presenting a case report of intraductal papilloma in an 18-year-old patient.